The Roles of Mesenchymal Stromal/Stem Cells in Tumor Microenvironment Associated with Inflammation - Drenka Trivanović; Jelena Krstić; Ivana Okić Djordjević; Slavko Mojsilović; Juan Francisco Santibanez; Diana Bugarski; Aleksandra Jauković (Hindawi Limited, 2016)
State of tumor microenvironment (TME) is closely linked to regulation of tumor growth and progression affecting the final outcome, refractoriness, and relapse of disease. Interactions of tumor, immune, and mesenchymal stromal/stem cells (MSCs) have been recognized as crucial for understanding tumorigenesis. Due to their outstanding features, stem cell-like properties, capacity to regulate immune response, and dynamic functional phenotype dependent on microenvironmental stimuli, MSCs have been perceived as important players in TME. Signals provided by tumor-associated chronic inflammation educate MSCs to alter their phenotype and immunomodulatory potential in favor of tumor-biased state of MSCs. Adjustment of phenotype to TME and acquisition of tumor-promoting ability by MSCs help tumor cells in maintenance of permissive TME and suppression of antitumor immune response. Potential utilization of MSCs in treatment of tumor is based on their inherent ability to home tumor tissue that makes them suitable delivery vehicles for immune-stimulating factors and vectors for targeted antitumor therapy. Here, we review data regarding intrusive effects of inflammatory TME on MSCs capacity to affect tumor development through modification of their phenotype and interactions with immune system.